Prevalence of anorexia nervosa among adolescent girls - Umarani, J; Annamalai, Anand Amirthraj (Bangladesh Journal of Medical Science, 2016)
Background: Girls tend to be more concerned about their physical appearance than boys during adolescent period. Adolescent girls are more likely to care for losing weight with the fear of being fat. Anorexia nervosa (AN), a form of self-starvation, is an eating disorder characterized by a distorted body image that leads to restricted eating and other behavior that prevents a person from gaining weight. It commonly occurs in teenage girls, although boys are also affected, especially in the prepubertal age group. Hence the researcher would like to assess the prevalence of anorexia nervosa among the adolescent nursing students. Objectives: 1. Determine the prevalence of anorexia nervosa among adolescent girls. 2. Find out the association between prevalence and selected demographic variables. Materials and Methods: The study was conducted among 100 B.Sc Nursing 1st year students at selected nursing colleges of Mangalore. The samples were selected by convenience sampling method. After obtaining informed consent and ethical clearance the data was collected by assessing the baseline proforma and Eating attitude Test. Findings: It was found that 31% of the adolescent girls were having high risk to anorexia nervosa and 69% were of no risk, whereas none of them were found consistent with anorexia nervosa. It was noted that all the 31 high risk girls were hostel residents. There was no association found between the risk of anorexia nervosa and the selected demographic variables. Conclusion: Some perceive anorexia as a simple case of vanity taken too far, but rather it is a complex psychological problem. So it is the responsibility of the teachers to create awareness among students by educating about the ill effects of anorexia nervosa which help us to prevent the incidence of anorexia nervosa and lead to healthy adolescents to the society. Bangladesh Journal of Medical Science Vol.15(3) 2016 p.466-470